Anchorage Offset Sensitivity Analysis of a Single Point Mooring System with a Moored Crude Oil Tanker in the Gulf of Guinea - Oghenethoja Umuteme; Charles U. Orji; Elakpa Augustine (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
Deepwater Single Point Mooring (SPM) systems increasingly integrate Steel Catenary Risers (SCRs) to enable high-pressure hydrocarbon transfer in water depths exceeding 500 m. While SCRs provide structural robustness, their high axial stiffness introduces strong coupling between seabed anchors and the surface buoy, significantly influencing system stability. This effect becomes critical in swell-dominated regions such as the Gulf of Guinea (GoG), where long-period waves (Tp ≈ 12–20 s) induce low-frequency surge motions of moored Very Large Crude Carriers (VLCCs), generating substantial loads that are transmitted through the tanker hawser to the buoy. This study numerically investigates the influence of anchorage offset on the mechanical response of a deepwater SPM–SCR system using a six-degree-of-freedom time-domain model developed in ANSYS Aqwa. The system comprises a cylindrical SPM buoy connected to a VLCC via a polyester hawser and restrained by six symmetrically arranged SCRs. Parametric simulations were performed for anchor offsets ranging from 500 m to 2,000 m under representative environmental conditions. Results reveal a pronounced nonlinear response governed by the transition of SCRs from seabed-supported catenary behaviour to a semi-taut configuration as offset increases. Beyond offsets of approximately 1,000–1,500 m, rapid amplification of riser tension occurs in offset-aligned legs, accompanied by large horizontal restoring forces and significant downward loads acting on the buoy. These vertical components can exceed the available buoyancy restoring capacity, indicating potential loss of hydrostatic stability. The polyester hawser exhibited slackening under large offsets, suggesting susceptibility to snap loading during dynamic excitation. The findings demonstrate that anchorage offset strongly governs load redistribution and stability in SCR-connected SPM systems, highlighting the need for optimized mooring footprint design to maintain structural compliance and safe offshore loading operations in deepwater swell environments.